2012
DOI: 10.1001/jama.2012.14144
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative High-Dose Dexamethasone for Cardiac Surgery

Abstract: clinicaltrials.gov Identifier: NCT00293592.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
271
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 372 publications
(313 citation statements)
references
References 23 publications
19
271
2
4
Order By: Relevance
“…increased in levels of creatine kinase myocardial band (RR = 1.22; 95% CI 1.07-1.38) [9]. In another trial (n = 4494), the RR for mortality was 0.92 (95% CI 0.57-1.49), for superinfection 0.64 (95% CI 0.54-0.75), for delirium 0.79 (95% CI 0.66-0.94), and for respiratory failure 0.69 (95% CI 0.51-0.94) in favor of dexamethasone (1 mg/kg perioperatively) [10]. See Appendix 2 in Supplementary material for evidence profile.…”
Section: Rationalementioning
confidence: 97%
“…increased in levels of creatine kinase myocardial band (RR = 1.22; 95% CI 1.07-1.38) [9]. In another trial (n = 4494), the RR for mortality was 0.92 (95% CI 0.57-1.49), for superinfection 0.64 (95% CI 0.54-0.75), for delirium 0.79 (95% CI 0.66-0.94), and for respiratory failure 0.69 (95% CI 0.51-0.94) in favor of dexamethasone (1 mg/kg perioperatively) [10]. See Appendix 2 in Supplementary material for evidence profile.…”
Section: Rationalementioning
confidence: 97%
“…In an isolated heart model, hydrocortisone significantly reduced the shedding of the endothelial surface layer after ischaemia, reperfusion and TNF-a infusion [22,36]. Prophylactic intra-operative glucocorticoids did not benefit patients undergoing cardiac surgery [49]. Similarly, the role of steroids in sepsis remains unclear: while glucocorticoids improve vasopressor efficacy, it is uncertain whether they benefit patients [50].…”
Section: Damage To the Endothelial Surface Layermentioning
confidence: 98%
“…80 Some studies have shown that a single prophylactic dose of dexamethasone can cause mild hyperglycemia for 24 hr postoperatively, although one randomized controlled trial found this was associated with a lower risk of some postoperative complications such as pneumonia and catheter-related infection. 81 Furthermore, a recent randomized controlled trial has refuted the claim that a single low dose of dexamethasone (up to 8 mg at induction of anesthesia) raises blood glucose concentrations for 24 hr after administration, as blood glucose levels did not differ from those observed after saline administration. 82 The exact dose of glucocorticoids at which potential harm outweighs benefit is unknown.…”
Section: Glucocorticoidsmentioning
confidence: 99%